Selection Method of Admission of Young Football Players to The Football Department (1 stage) - Karimov A.K. (Euro Asian Journal Publishing, 2023)
The article provides information on the selection of young players for the training of football players. Along with this, tests are given for selection and its standards are indicated. Based on the selection, it is indicated that children can be selected based on the sum of their scores.
Keywords: football; selection; methodology; test